L’Italie selon Shakespeare et Ben Jonson : l’altérité dans un théâtre sans décor - Christophe Camard (Revue LISA)
This article proposes an analysis of the image of the Italian in the plays of Shakespeare and Ben Jonson, for Italy figures as a privileged setting in the works of both authors. The representation of a country unknown to the majority of the spectators and to a play’s author, in a theatre with little decor, is necessarily transmitted through a collection of images — physical, geographical, cultural, and also linguistic. The border between a realistic image and a simple stereotype is marked by a fine line: when does a representation of the Other become a cliché and when is it founded on more substantial knowledge, or, at least, informed by sources that allow for a methodological development of knowledge of this Other? This is the question upon which we have based this exploration of Shakespearean drama. We will highlight the fundamental difference between the plays of Ben Jonson and those of Shakespeare in their representation of Italy and of the Italian and, therefore, in their use of the imagery in question. Indeed, the image of Italy and the Italian, frequent in Jonson’s writing, demonstrates a certain precision in his research, but is, finally, closer to a clichéd portrayal than is the case with Shakespeare who appears both conscientious about the authenticity of his portrayal and conscious of the role of his imagination in its construction. For the purpose of this analysis, we will present most of the images that comprise the representation of this Italian stranger in the plays of Shakespeare and Jonson and the source material that may have informed them.